Analysis and evaluation of magnetism of black toners on documents printed by electrophotographic systems. (October 2016) - Biedermann, A.; Bozza, S.; Taroni, F.; Fürbach, M.; Li, B.; Mazzella, W.D.
Abstract : Highlights: Magnetic properties of different black toner specimens were measured and compared. Analysis of magnetism is complementary to traditional methods such as FTIR. Analysis of magnetism is realistically applicable in closed set cases. Graphical probabilistic models are useable for evaluating measurement results. Abstract: This paper reports on a study to assess the potential of measurements of magnetism, using a proprietary magnetic analysis system, for the routine analysis of toners on documents printed by black and white electrophotographic systems. Magnetic properties of black toners on documents printed by a number of different devices were measured and compared. Our results indicate that the analysis of magnetism is complementary to traditional methods for analysing black toners, such as FTIR. Further, we find that the analysis of magnetism is realistically applicable in closed set cases, that is when the number of potential printing devices can be clearly defined.